The effects of socialization on dogs - Swanson, Sara (Kansas State University, 2020)
Problem behaviors in domestic dogs (Canis lupis familiaris) can affect owner contentment and the human-animal bond as owners try to navigate management of their pet’s behaviors. While some problem behaviors can be a result of either poor or lack of appropriate training exercises, others can also be rooted in fear. These fear-based behaviors, such as aggression and anxiety, have an ontological aspect where the potential for development for these behaviors can be linked to distress or lack of desensitization during primary social development. These behaviors have a significant effect on the human-animal bond. A large percentage of animals (approximately 30%) are surrendered each year, primarily due to fear-based behaviors, including aggression. This report culminates research and science behind the developmental stages of the domestic dog and examines how various human interventions within these stages can result in a positive effect on the dog’s adult behavior and reducing the likelihood of fear-based behaviors.
Keywords: dog; socialization; fear; behavior